2015
DOI: 10.1002/asia.201500942
|View full text |Cite
|
Sign up to set email alerts
|

A Remarkably Efficient MnFe2O4‐based Oxidase Nanozyme

Abstract: Nanomaterials-based enzyme mimetics (nanozymes) have attracted considerable interest due to their applications in imaging, diagnostics, and therapeutic treatments. Particularly, metal-oxide nanozymes have been shown to mimic the interesting redox properties and biological activities of metalloenzymes. Here we describe an efficient synthesis of MnFe2 O4 nanomaterials and show how the morphology can be controlled by using a simple co-precipitation method. The nanomaterials prepared by this method exhibit a remar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(58 citation statements)
references
References 30 publications
(24 reference statements)
3
55
0
Order By: Relevance
“…It is interesting to note that while many peroxidase nanozymes were reported (i.e., using H2O2 as a cosubstrate), very few have oxidase activity. 9,[19][20][21][22][23] The best known examples are gold nanoparticles for glucose oxidation, 9 and CeO2 nanoparticles (nanoceria) that oxidize a diverse range of substrates. 20 Oxidase nanozymes are important since they do not require unstable H2O2 as a co-substrate.…”
mentioning
confidence: 99%
“…It is interesting to note that while many peroxidase nanozymes were reported (i.e., using H2O2 as a cosubstrate), very few have oxidase activity. 9,[19][20][21][22][23] The best known examples are gold nanoparticles for glucose oxidation, 9 and CeO2 nanoparticles (nanoceria) that oxidize a diverse range of substrates. 20 Oxidase nanozymes are important since they do not require unstable H2O2 as a co-substrate.…”
mentioning
confidence: 99%
“…Finally, in case of O 1 s peaks, we observed unusual bond splitting into two peaks (529.8 and 532.8 eV) which denotes that the formation of ionic bonds between metals (Mn/Fe) with oxygen and hydroxyl group respectively. These results suggested that the Mn and Fe are in the oxidation state of +2 and +3 ions respectively [8,24,31,32].…”
Section: Resultsmentioning
confidence: 88%
“…20 Verneker et al developed an efficient synthesis of MnFe 2 O 4 via a co-precipitation method with controlled morphology; it showed remarkable oxidase mimetic properties. 21 Graphene quantum dot-Ag nanoparticles show high oxidase and antibacterial properties for Gram-negative, Gram-positive and drug-resistant bacteria. 22 Cerium oxide was also studied for pH-tuneable oxidase activity for cancer folate biomarker sensors.…”
Section: Introductionmentioning
confidence: 99%